Graphic Activism on WeChat: The Aesthetics of Dissent in the Age of COVID-19. (20th January 2021) - Ma, Ruimin
Abstract: The special conditions imposed by quarantine have shifted much critique and dissent regarding government policy onto the internet. This visual essay presents a series of screenshots which document manifestations of public dissent that appeared on WeChat in the early part of 2020 in China. These screenshots reveal the graphic tactics that were used to express dissent, as well as the dynamic sociopolitical context inhabited by Chinese netizens during the early days of the pandemic. This project adds to an understanding of the state of politics, technology, and culture of China's cyberspace during the onset of COVID-19. Link to Video Essay The video file for this article can be accessed at https://doi.org/10.1080/17547075.2021.1875543